ANALISIS KINERJA PERBANKAN DI INDONESIA SEBELUM DAN SESUDAH PENGALIHAN FUNGSI PENGATURAN DAN PENGAWASAN PERBANKAN DARI BANK INDONESIA KE OTORITAS JASA KEUANGAN (STUDI PADA PERBANKAN BUMN DAN PERBANKAN YANG MELAKUKAN MERGER DAN AKUISISI LINTAS NEGARA) - Reza, M. Fachrul; Rokhmawati, Andewi (Jurnal Tepak Manajemen Bisnis, 2018)
The purpose of this study to determine differences in the performance of banks in Indonesia, especially BUMNâs Banking and Banking implementing Merger and Acquisition Cross Country, using the study period of 2 years before and 2 years after the transfer of regulatory and supervisory functions Perbankan dari Bank Indonesia to the Financial Services Authority.The population in this study are all BUMNâs Banking and Banking conducting mergers and acquisitions by foreign parties from 2012 to 2015. The sample used in this study was 14 Bank which consists of 4 BUMNâs Banking and 10 Banking conducting Transnational Merger and Acquisition . Methods of data analysis research using purposive sampling method by using paired sample t-test analysis and independent sample t-test.The result of research shows that BUMNâs Banking only BOPO and LDR variables are significant, while CAR, NPL and ROA variables are not significantly different. In Banking that perform merger and Acquisition of Cross Country only variable of NPL, ROA and BOPO there are significant difference whereas CAR and LDR variable there is no significant difference. In the BUMNâs Banking and Banking implementing Merger and Acquisition Cross Country After Transfer of functions Regulation and Supervision of Banking of Bank Indonesia to the Financial Services Authority, only ROA and BOPO that there are significant differences, while variable CAR, NPL and LDR is not a significantdifference .